Long or short silicic magma residence time beneath Hekla volcano, Iceland? - Sigmarsson, Olgeir; Bergþórsdóttir, Ingibjörg; Devidal, Jean-Luc; Larsen, Gudrún; Gannoun, Abdelmouhcine (Contributions to Mineralogy and Petrology, 2022)
co-auteur étranger International audience Timescales of magma transfer and diferentiation processes can be estimated when the magma diferentiation mechanism is known. When conventional major and trace element analyses fail to distinguish between various processes of magma diferentiation, isotope compositions can be useful. Lower Th isotope ratios in silicic relative to basaltic magmas at a given volcano could result from magma storage over a period of several tens of thousands of years, or if the diferentiation process was fractional crystallization alone, or from crustal anatexis on a much shorter timescale. Recently mapped bimodal tephra layers from Mt. Hekla, Iceland, confrm lower (230Th/232Th) and higher Th/U in silicic versus mafc magmas. Higher Th/U has been taken to indicate either apatite fractionation or partial crustal melting. In situ trace element analysis of apatite and the enveloping glass in basaltic andesite, dacite and rhyolite was undertaken to examine its capacity to fractionate trace elements and their ratios. Both Th and U are compatible in apatite with a partition coefcient ratio DU/DTh of 1. Hence, apatite crystallization and separation from the melt has a negligible efect on Th/U in Hekla magmas. Partial melting of hydrothermally altered crust remains the preferred mechanism for producing silicic melt beneath Hekla. Ten to twenty percent partial melting of metabasaltic crust with 0.4–1.2 wt% H2O produces dacite magma with 4–6% water. Absence of low δ18O values in Hekla magmas compared to silicic magmas of the rift zones suggests mild hydration of the hydrothermally altered crust. Silicic magma formation, storage, diferentiation and eruption at Hekla occurred over a timescale of less than a few centuries. Decreasing production of rhyolite and dacite during the Holocene lifetime of Hekla suggests changes in the crustal magma source and readjustment of the magma system with time.